Things We've Learnt About Communication - Sellen, Abigail; Harper, Richard (Things We've Learnt About, 2011)
“Things We’ve Learnt About..” is a publication from the Human Experience & Design team that summarises our work around a specific theme in a way that we hope is interesting, insightful and inspirational.